XALÍQTÍ ÚYRENIWDIŃ TARIYXÍY-GEOGRAFIYALÍQ DEREKLERI - Utepova, G.B. (SCIENCE and SOCIETY, 2022)
In this article, there are various controversial opinions about the areas where the people lived in the most ancient historical periods, their number and dynamics, as well as the geographical distribution of their unique characteristics in their natural growth.